SPE Annual Technical Conference and Exhibition 2005
DOI: 10.2118/95826-ms
|View full text |Cite
|
Sign up to set email alerts
|

Achieving True Sandstone Reservoir Stimulation in Deepwater Horizontal Wells

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractIn offshore horizontally completed wells, an acid job is usually pumped to remove the filter cake, previously created to allow sand control equipment and gravel be placed across the entire extended section. When such wells are acidized to remove the filter cake with a hydrochloric: hydrofluoric acid mixture, the resulting skin values are still in the positive range.An improved HF acid system has been introduced in the Campos Basin-offshore Brazil with outstan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Results demonstrated that IHHFAS can not only remove the filter cake, but also stimulate the formation more appreciably that the RHHAM (Mendes et al, 2005). Table 2 shows a typical acid treatment with IHHFAS applied to improve injection in Campos and Espirito Santo Basins.…”
Section: ) Typical Acid System Treatmentmentioning
confidence: 99%
“…Results demonstrated that IHHFAS can not only remove the filter cake, but also stimulate the formation more appreciably that the RHHAM (Mendes et al, 2005). Table 2 shows a typical acid treatment with IHHFAS applied to improve injection in Campos and Espirito Santo Basins.…”
Section: ) Typical Acid System Treatmentmentioning
confidence: 99%